Two new species of Lachesilla in the andra group, from the Chapada Diamantina, Bahia, Brazil (Psocodea: ‘Psocoptera’: Lachesillidae) - Aldrete, Alfonso N. García; Da Silva Neto, Alberto Moreira (Zootaxa, 2013)
Two new species of Lachesilla in the andra group are described from Brazil, where the group was previously unknown. They raise to five the number of species in the group known in South America. An identification key for females of the andra group in South America is included.